Bamboo-biochar and hydrothermally treated-coal mediated geochemical speciation, transformation and uptake of Cd, Cr, and Pb in a polymetal(iod)s-contaminated mine soil. (October 2020) - Mujtaba Munir, Mehr Ahmed; Liu, Guijian; Yousaf, Balal; Ali, Muhammad Ubaid; Cheema, Ayesha Imtiyaz; Rashid, Muhammad Saqib; Rehman, Abdul
Abstract: In this study, polymetal(iod)s-contaminated mining soil from the Huainan coalfield, Anhui, China, was used to investigate the synergistic effects of biochar (BC), raw coal (RC), and hydrothermally treated coal (HTC) on the immobilization, speciation, transformation, and accumulation of Cd, Cr, and Pb in a soil–plant system via geochemical speciation and advanced spectroscopic approaches. The results revealed that the BC-2% and BC–HTC amendments were more effective than the individual RC, and/or HTC amendments to reduce ethylene-diamine-tetraacetic acid (EDTA)-extractable Cd, Cr, and Pb concentrations by elevating soil pH and soil organic carbon content. Soil pH increased by 1.5 and 2.5 units after BC-2% and BC–HTC amendments, respectively, which reduced EDTA-extractable Cd, Cr, and Pb to more stabilized forms. Metal speciation and X-ray photoelectron spectroscopy analyses suggested that the BC–HTC amendment stimulated the transformation of reactive Cd, Cr, and Pb (exchangeable and carbonate-bound) states to less reachable (oxide and residual) states to decrease the toxicity of these heavy metals. Fourier transform infrared spectroscopy and X-ray diffraction analyses suggested that reduction and adsorption by soil colloids may be involved in the mechanism of Cd(II), Cr(VI), and Pb(II) immobilization via hydroxyl, carbonyl, carboxyl, and amide groups in the BC and HTC. Additionally, the BC-2% and BC–HTC amendments reduced Cd and Pb accumulation in maize shoots, which could mainly be ascribed to the reduction of EDTA-extractable heavy metals in the soil and more functional groups in the roots, thus inhibiting metal ion translocation by providing the electrons necessary for immobilization, compared to those in roots grown in the unamended soil. Therefore, the combined application of BC and HTC was more effective than the individual application of these amendments to minimize the leaching, availability, and exchangeable states of Cd, Cr, and Pb in polymetal(iod)s-contaminated mining soil and accumulation in maize. Graphical abstract: Image 1 Highlights: Cd, Cr, and Pb adsorption capacity enhanced by combined application of biochar and hydrothermally treated coal. Biochar and hydrothermally treated coal increased surface functionality, SOC, and pH in the soil. Combined application of both reduced the exchangeable fractions of heavy metals. Application of biochar and hydrothermally treated coal reduced plants metal uptake. Hydrothermally treated coal with biochar could be served as a novel cost-effective soil amendment.